FULFILLING INNOVATIVE POTENTIAL IS A PRIORITY FOR BELGOROD STATE NATIONAL RESEARCH UNIVERSITY - Igor S. Konstantinov; Andrey P. Peresypkin; Larisa V. Verzunova (Высшее образование в России)
The article considers the dynamics of the research and innovation potential of Belgorod State National Research University (BelSU) in recent years and the main achievements of the University in research and innovation; it also looks at the experience acquired and the examples of effective commercialization of the intellectual activity results of BelSU research units within the framework ofthe project integration with economic entities of the country and the region. The authors pay special attention to the establishment of BelSU as a research entrepreneurial university, which involves building up its research capacity, first of all, in the spheres of materials science, living systems, and information and communication technologies, as well as forming an effective innovation ecosystem.